HUBUNGAN GAYA HIDUP TERHADAP PREMENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI SMA NEGERI 1 BANJIT PROVINSI LAMPUNG - Liandani, Meri (Jurnal Kesehatan, 2022)
Premenstrual syndrome is a collection of physical symptoms, psychological and lifestyle factors that happen in pramenstrualisasi. The cause of PMS is still unknown, but lifestyle may play a role in PMS event. The purpose of this study was to determine the relationship of lifestyle of the teeneger pramenstrual in SMA Negri 1 Banjit Lampung province. This research uses a quantitative method with cross sectional approach. in this study sample was 60 students by using total sampling technique. data collection using questionnaires. data analysis covering univariate and bivariate analysis. based on the results of the univariate that teeenger who experience premenstrual syndrome as many (60%), the physical changes as much (60%), experienced a change in psychology (58.3%), and poor lifestyle as much (54.1%). the results analysis of research data with static techniques chi square test at the significant level of 5% (). Bivariate results with variable lifestyle (p = 0.013 OR = 4.545). the conclusion of life-style relate to teeneger girls premenstrual syndrome before menstruation.